AI and machine learning - Rahman, Was (New Delhi SAGE Publications India Pvt Ltd, 2020)
"This book is grounded in facts rather than opinions. It illustrates and explains using generally accepted knowledge and the author's personal experience. It refrains as far as possible from offering views other experts would take issue with. The goal is to retain a measured, neutral voice on a topic that doesn't always lend itself to that. The book doesn't tell you how to build AI or ML systems, or advise on what to do about it in your business. Nor does it dig into details that require deep technical or specialist knowledge. It's a concise introduction to a complex subject. So by design, it doesn't explore in depth the intricacies and nuances of the topics. Nor does it elaborate in detail on the "why" and "how" behind what it describes. If you're interested in further detail, there's a comprehensive set of references. They're a mix of academic, general and specialist references to more in-depth coverage of the ideas and information covered"--
Includes bibliographical references.
Keywords: Artificial intelligence; Machine learning